E-Cigarette Use Among Adolescents: An Overview of the Literature and Future Perspectives - Perikleous, Evanthia P.; Steiropoulos, Paschalis; Paraskakis, Emmanouil; Constantinidis, Theodoros C.; Nena, Evangelia (Frontiers in Public Health, 2018)
Background: Electronic cigarettes (e-cigarettes) are rapidly emerging into a new trend among adolescents, signaling a new époque, that of vapers. E-cigarettes are battery-powered nicotine delivery devices that heat a typically flavoring liquid solution into an aerosol mist that users inhale, allowing them to imitate the act of conventional smoking. There are concerns about the impact of e-cigarettes at both individual and public health level. Aim: To discuss the characteristics of the most vulnerable, to become e-cigarette users, group of adolescents and to further highlight their behaviors and characteristics. Methods: An electronic search in PubMed, EMBASE, and Google Scholar databases was conducted, using combinations of the following keywords: adolescents, teenagers, e-cigarettes, electronic cigarettes, vaping. The search included all types of articles written in English until August 2017. A total of 100 articles were found, and 25 were finally included in the present review. Results: Older age, male gender, conventional smokers, peer influence, daily smoking, and heavier smoking are the most common characteristics of adolescent e-cigarette users. Conclusions: E-cigarette use is common, especially between certain subgroups in the adolescent population. Since e-cigarette use is increasing and considering that the long term health effects are still under investigation, targeted interventions towards more susceptible individuals may be an effective prevention strategy.